The concept of “Kampus Merdeka” in the current policy of Indonesian higher education: ELT lecturers’ perspectives - Sukirman Sukirman (Institut Agama Islam Negeri Palopo, 2022)
This study aims to advance global readers’ understanding of current Indonesian higher education policy associated with students’ rights. The researcher conducted document analysis on official regulations and interviewed lecturers to gain data about their response on the policy. The most obvious findings to emerge from this study that the Indonesian government tries to address the global challenges of higher education by transforming the paradigm of learning limited not to only classroom activities, instead providing flexibility for students to learn outside the classroom. Students should have flexibility to explore their competences by applying directly to either the societies or workplaces. Students should realise that experience is the best life-teacher to lead them to be independent and strong individuals. Learning should not always take place in the classroom; however, every place can be a medium for learning, since nature is the source of learning. Regardless the participants’ views on the current policy as the impacts neoliberal ideology, this transformation is supposed to provides positive impacts not only on students’ personal but also social, academic, and ethical domains by balancing their academic and social lives. In addition, the current policy is also intended to prepare students to respond global competitiveness and rapidly transforming societies, workplaces, and environments by mastering demanding competencies in the 21st century. Therefore, rapidly curriculum adjustment is always needed in responding any social phenomena that may significantly affect the policy making of educational system, as contextualised by the present study from Indonesian context dealing with the demands to conduct ELT curriculum adjustment as the response on the current policy. The implications of the findings are further discussed.Keywords: Higher education; Indonesian higher education policy; Kampus Merdeka; Students’ rights